Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the equation [tex]\(6^{2x + 2} \cdot 6^{3x} = 1\)[/tex] step-by-step.
1. Combine Exponents:
Given the property of exponents [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex], we can combine the exponents on the left-hand side.
[tex]\[ 6^{(2x + 2)} \cdot 6^{3x} = 6^{(2x + 2 + 3x)} = 6^{(5x + 2)} \][/tex]
So the equation now looks like:
[tex]\[ 6^{5x + 2} = 1 \][/tex]
2. Interpret the Exponential Equation:
Recall that any non-zero number raised to the power of 0 is 1. Hence, we need the exponent on the left to be zero for the entire term to equal 1.
[tex]\[ 6^{0} = 1 \][/tex]
Therefore, we set the exponent equal to 0:
[tex]\[ 5x + 2 = 0 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
Subtract 2 from both sides:
[tex]\[ 5x = -2 \][/tex]
Divide both sides by 5:
[tex]\[ x = \frac{-2}{5} \][/tex]
Hence,
[tex]\[ x = -0.4 \][/tex]
So the solution to the equation [tex]\(6^{2x + 2} \cdot 6^{3x} = 1\)[/tex] is
[tex]\[ x = -0.4 \][/tex]
1. Combine Exponents:
Given the property of exponents [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex], we can combine the exponents on the left-hand side.
[tex]\[ 6^{(2x + 2)} \cdot 6^{3x} = 6^{(2x + 2 + 3x)} = 6^{(5x + 2)} \][/tex]
So the equation now looks like:
[tex]\[ 6^{5x + 2} = 1 \][/tex]
2. Interpret the Exponential Equation:
Recall that any non-zero number raised to the power of 0 is 1. Hence, we need the exponent on the left to be zero for the entire term to equal 1.
[tex]\[ 6^{0} = 1 \][/tex]
Therefore, we set the exponent equal to 0:
[tex]\[ 5x + 2 = 0 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
Subtract 2 from both sides:
[tex]\[ 5x = -2 \][/tex]
Divide both sides by 5:
[tex]\[ x = \frac{-2}{5} \][/tex]
Hence,
[tex]\[ x = -0.4 \][/tex]
So the solution to the equation [tex]\(6^{2x + 2} \cdot 6^{3x} = 1\)[/tex] is
[tex]\[ x = -0.4 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.